Political Islam: By Charles Butterworth and I. William Zartman, eds. Annuls of the American Academy of Political and Social Science, no. 524 (November 1992). (American Journal of Islam and Society, 1994)
This volume surveys the complex roles Islamic ideologies play in thepolitics of the Muslim world. The authors are distinguished scholars inIslamic history, philosophy, and law as well as specialists in the sociologyand politics of various Muslim countries. Despite their varied disciplinarybackgrounds and the vastness of their subject, the book features aremarkable degree of interconnection and does not sacrifice the analyticalspecificity needed for each essay.The volume's fourteen articles ate grouped into six broad categories:History of Islamic Political Theory and Practice. These essays offer twointerpretive histories of the evolution and cutrent status of Islam's role inthe political sphere. Ira Lapidus argues that Islamic political theory hasbeen governed by two paradigms, each grounded in a separate vision ofthe Islamic "golden age." The first paradigm is the "seamless" Islamicethos, a holistic conception of law, politics, and personal morality thatexisted at M a d i i under the Prophet and his four immediate politicalsuccessots. Even though this period lasted for barely four decades, it continuesto serve as the vision of the Islamic ideal, especially for the recurrentrevivalist movements and thinkes who have based their appealsupon this "first golden age." The second paradigm is chatactenzed by diffemtiatedreligious and secular institutions. Despite attempts by medievaljurists to maintain the theoretical church-state unity, Islamic Societies developedtacit and clearly articulated spheres of religious and secularauthority. This made it possible for the early Islamic empires to absorband then live with non-Islamic traditions and peoples (i.e., Persians andTurks). This "second golden age" is epitomized by the Ottoman Empire,which nxognized Islam as the "official" religion and whose ruler was acceptedas the titular caliph. Nevertheless, the fusion of teligion andpolitics was never complete, as reflected in the emergence of distinctly"religious" institutions parallel to those of the state.Modem Muslim states, Lapidus argues, are proof of the triumph ofthe second over the first paradigm. "Modern states can be seen as anexpression of the historical separation of state and Islam .... All hope ofsalvation has been concentrated in the nonstate realm, in the religio-civilcommunity, and in personal piety" (p. 23). As a result, states are notviewed by their own people, by and large, as the bearers of their religious ...